A fully coupled analysis of unsteady aerodynamics impact on vehicle dynamics during braking. Issue 1 (1st January 2019) - Broniszewski, Jakub; Piechna, Janusz
Abstract : This study investigates the impact of unsteady aerodynamic loads on the behavior of car dynamics during braking maneuvers. In the analysis, two independent solvers were coupled to solve an existing fluid structure interaction (FSI) problem. Transient CFD analysis applying Fluent software was used to obtain realistic aerodynamic loads. A full car, nonlinear dynamic model with elastic suspension system was built in a dedicated multibody dynamic system MSC.Adams/Car. Both physics were integrated into one ecosystem via a block diagram environment for multidomain simulation (Matlab/Simulink). Methodology elements were validated against experimental results for a rectangular beam in cross-flow with vortex-induced vibrations. The final results were validated against a full-scale experiment on a real car. The solution of an untypical flow problem (decreasing car speed during a braking maneuver) required an untypical reference frame. The classic case, with an observer at rest (stationary model and moving air), was replaced with a moving observer. The whole domain was translocated during the analysis with a velocity which varied with time. The problem was further complicated by the presence of movable aerodynamic elements. The overset mesh technique was used to allow movement of the car body and active aerodynamic surfaces. The results obtained show the importance of aerodynamic effects on the braking process. It was shown that in the analyzed scenario, movable aerodynamic features can reduce the distance to stop by 6%. The complex interaction between the active aerodynamic surface and the car body with respect to load split is discussed as well. The methodology proposed to determine the behavior car dynamics with unsteady aerodynamic effects taken into account appears to be a significant improvement when compared with existing methodologies used for such an assessment.